In vitro activity of ceftaroline against mecC-positive MRSA isolates. (June 2016) - Armengol-Porta, Marc; Tenorio-Abreu, Alberto; Bandt, Dirk; Coleman, David C.; Gavier-Widen, Dolores; Hotzel, Helmut; Kinnevey, Peter; Lazaris, Alexandros; Peters, Martin; Rangstrup-Christensen, Lena; Schlotter, Katharina; Shore, Anna C.; et al.
Highlights: We determined the MICs of the novel cephalosporin compound ceftaroline against a collection of MRSA harbouring mecC /SCC mec XI. Isolates were found to be susceptible to ceftaroline. Abstract: Ceftaroline is a new cephalosporin with activity against methicillin-resistant Staphylococcus aureus (MRSA). A collection of 17 clinical and veterinary mecC -positive MRSA isolates was tested to evaluate the in vitro efficacy of ceftaroline against recently emerged mecC -MRSA isolates. Minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) of ceftaroline for the 17 isolates were determined by broth microdilution using the methodology and interpretive criteria of the Clinical and Laboratory Standards Institute (CLSI). Additional susceptibility tests were performed using ceftaroline M.I.C.Evaluator (M.I.C.E.™) strips. All isolates showed susceptibility according to CLSI breakpoints, with MICs of ceftaroline ranging from 0.125 mg/L to 0.25 mg/L. MBCs were identical or up to a twofold dilution step higher. In conclusion, all tested isolates, from various sources and belonging to several clonal complexes (CCs), but predominantly to CC130, were found to be susceptible to ceftaroline. Ceftaroline could thus be an option for the treatment of mecC -MRSA infections.